Dendritic inhibition mediated by O-LM and bistratified interneurons in the hippocampus - Müller, Christina; Remy, Stefan (Frontiers in Synaptic Neuroscience, 2014)
In the CA1 region of the hippocampus pyramidal neurons and GABAergic interneurons form local microcircuits. The CA1 interneurons are a diverse group consisting of many subtypes, some of which provide compartment-specific inhibition specifically onto pyramidal neuron dendrites. In fact, the majority of inhibitory synapses on pyramidal neurons is found on their dendrites. The specific role of a dendrite-innervating interneuron subtype is primarily determined by its innervation pattern on the distinct dendritic domains of pyramidal neurons. The efficacy of dendritic inhibition in reducing dendritic excitation depends on the relative timing and location of the activated excitatory and inhibitory synapses. In-vivo, synaptic properties such as short-term plasticity and neuro-modulation by the basal forebrain, govern the degree of inhibition in distinct dendritic domains in a dynamic, behavior dependent manner, specifically during network oscillation such as the theta rhythm. In this review we focus on two subtypes of dendrite-innervating interneurons: the oriens-lacunosum moleculare (O-LM) interneuron and the bistratified interneuron. Their molecular marker profile, morphology, and function in-vivo and in-vitro are well studied. We strive to integrate this diverse information from the cellular to the network level, and to provide insight into how the different characteristics of O-LM and bistratified interneurons affect dendritic excitability, network activity and behavior.